ANALISIS PENGARUH PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN MUARA ENIM - Anton Indra Budiman; Ermadiani Ermadiani; Ubaidillah Ubaidillah (AKUNTABILITAS, 2021)
This study aims to determine and analyze the effect of local tax revenue and levies on the increase in local revenue in Muara Enim. This study uses a sample from the regional government APBD report of Muara Enim Regency, namely data on PAD, regional taxes, levies, and other revenues. other data obtained from the Regional Revenue Agency of Muara Enim Regency for the period 2016-2018 .. The data analysis was carried out by classical assumption tests and hypothesis testing using the multiple linear regression method. The results of this study indicate that local tax revenue has a significant positive effect on the increase in local revenue in Muara Enim Regency. Meanwhile, the local retribution does not have a significant effect in increasing the local revenue of Muara Enim Regency